2022
DOI: 10.3390/jfmk7010020
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Hyaluronic Acid versus High Molecular Weight Hyaluronic Acid for the Treatment of Hip Osteoarthritis in Overweight/Obese Patients

Abstract: Background: Obesity is the main risk factor for hip osteoarthritis, negatively affecting the outcome of the disease. We evaluated the effectiveness of viscosupplementation with hybrid hyaluronic acid compared to that with high molecular weight hyaluronic acid in overweight/obese patients with hip osteoarthritis (OA). Methods: 80 patients were divided into two groups: a treatment group received two ultrasound-guided intra-articular hip injections of hybrid HA 15 days apart; a control group received a single ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Fourth, the double size of particles (HMW has very good rheological properties due to LMW, which triggers endogenous HA production by stimulation of fibroblasts). Lastly, participants in previous studies showed very good tolerance of the product administered together with PRP and no cytotoxic effect [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, the double size of particles (HMW has very good rheological properties due to LMW, which triggers endogenous HA production by stimulation of fibroblasts). Lastly, participants in previous studies showed very good tolerance of the product administered together with PRP and no cytotoxic effect [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…Indigenously, high-molecular-weight (HMW) HA is found, which is then degraded into smaller fragments of low molecular weight (LMW) depending on the environmental factors [ 48 , 49 ]. This degradation of HA is essential for a number of bodily functions, for instance, as a lubricant in the synovial fluid [ 48 , 50 ].…”
Section: Ha and Inflammation: Influence Of Molecular Weightmentioning
confidence: 99%
“…The manipulation of MW of HA in drug delivery systems can lead to analgesic, anti-inflammatory and immunostimulatory results [ 48 , 49 , 50 , 51 ]. Although there is a lack of detailed research on the specificity of the antinociceptive effects of HA of different MW, it is widely accepted that HMW HA inhibits the activation of lipopolysaccharide (LPS) by directly binding to the toll-like receptor-4 (TLR-4) under inflammatory conditions [ 52 ].…”
Section: Ha and Inflammation: Influence Of Molecular Weightmentioning
confidence: 99%
“…Surgical intervention also has much greater risks than other less invasive interventions. Evidence demonstrates that less invasive OA interventions such as intra-articular injections are effective at improving physical function, provide pain relief, and bolster quality of life ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%